Analisis Pemanfaatan Teknologi Dalam Pengelolaan Dokumen Warga Binaan Pemasyarakatan - Maula, Rayinda Estri (Syntax Literate, 2020)
This research aims to analyze the utilization of technology in the framework of the implementation of confidential documents such as the data of prison community. The research is backed by the abundance of data on the target citizens who have to be processed and archived structured from the period of detention in the stage of investigation, prosecution and up to the fall of the criminal ruling, as well as the management of the data of the target citizens To be processed in order to grant the rights of the target citizen in the construction period in correctional institution. Information technology is used to assist criminal calculations and the management of digital data archives, thus creating accountable, precise and transparent public information. Based on the problems that arise from current issues, we use the theory and review of the literature on management of information technology-based data. The study includes understanding, objectives, and utilization indicators that can be adopted by the system management and archisiation of community-building people. Proposed hypothesis: Information technology affects data management and conversion by digitizing methods so that data can be integrated. From the results of this research, there is a conclusion that information technology presents a useful element for the management and conversion of the Community data workers and the influence on the integrated work pattern.